Analisis Pengaruh Customer Relationship Management (CRM) Terhadap Customer Satisfaction dan Customer Loyalty : Studi Pada Pengguna Dompet Digital Go-Pay Di Pekalongan - Laelatul Maulida; Wenti Ayu Sunarjo; Rengga Kusuma Putra (Jurnal Bisnis Inovatif dan Digital, 2024)
This research aims to determine the effect of Customer Relationship Management (CRM) on Customer Satisfaction and Customer Loyalty on the Gopay e-wallet in Pekalongan and its surroundings. This type of research is quantitative with a purposive sampling technique using a questionnaire distributed to 50 Gopay users in Pekalongan and surrounding areas. This research uses multiple regression analysis methods, classical assumption tests, t tests, and R2 square tests, using SPSS V.20. Partial test results show that Customer Relationship Management has a positive and significant effect On Customer Satisfaction and Customer Loyalty.